From the History of the Empire to World History the Historiographical Itinerary of Christopher A. Bayly - Maurizio Griffo (Clio: Essays in History, Archaeology and Art History, 2019)
This volume is the outcome of a conference on the work of Christopher Bayly held in Naples on March 2016. At less than one year from his untimely death, the convenors called on a group of specialists in several disciplinary areas, on which Bayly has left his enduring mark, to collaborate on a first survey of the rich and complex scientific legacy of the English historian. Each essay focuses on one of the extraordinary succession of great works by which he pioneered innovative approaches throughout his academic career. The collection as a whole provides therefore an account of Bayly's foremost contributions to the different scholarly fields in which he made repeated breakthroughs, over a period of five decades, on some of the most advanced research fronts of international historiography: the local roots of Indian nationalism, the transition from pre-colonial to colonial India and the role of indigenous society in the establishment of European domination, the nature and limits of colonial power, the rise of the Second British Empire, the history of globalization and the nineteenth-century turn towards planetary modernity, the transregional development of liberalism and nationalism. The common aim of the authors is to highlight the stages of the path through which Bayly emerged, at the beginnings of the 2000s, as a key figure in the current revival and renewal of world history.